PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA KORUPSI DAN PERHITUNGAN KERUGIAN KEUANGAN NEGARA BERDASARKAN UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG TINDAK PIDANA KORUPSI - Ferra, Ferra; Tanoto, Stephanie; Lifia, Maliny (JURNAL MERCATORIA, 2019)
Corruption is an extraordinary crime (extraordinary crime) that provides benefits for yourself by abusing the position of another party, where the act is not done alone and usually involves more than one person. Unlike the case with the crime of money laundering and bribery. This research is descriptive. Sources obtained are secondary legal material, the data is obtained from literature in the form of legal books, legal journals, and legal articles. Factors that encourage the occurrence of criminal acts of corruption usually originate from internal factors, namely the perpetrators themselves or external factors, namely from outside the perpetrators. To find out whether or not there is a criminal act of corruption, several financial calculation methods are made, namely the total loss method (the state financial loss method), the net loss method (the net loss method), the fair price method, and the cost price method. Law enforcement and the amount of recovery of state financial losses can be seen in the Corruption Act.